Growth versus the Environment: Is there a Trade-off? - Kågeson, Per (Economy & Environment, 1998)
Economic growth and the environment is a complex and much debated issue. Per Kågeson's book has a broader approach than earlier studies on this subject as he relates the analysis of present-day problems and trends (1960-2010) to clearly defined long-term objectives based on the concept of sustainable development. The present volume covers the use of non-renewable resources in the OECD countries in a global perspective, while the regional environmental impact of economic growth is discussed in a European context. The book also includes an analysis of the potential conflict between pollution abatement costs and economic growth